Chemotherapy of advanced non-small-cell lung cancer: current landscape. (March 2013) - Pallis, Athanasios G; Dziadziuszko, Rafal; O'Brien, Mary
Non-small-cell lung cancer represents the leading cause of cancer-related death in the western world. Unfortunately, the majority of patients are diagnosed with advanced, unresectable disease that remains incurable, while most patients who are treated with curative intent will eventually develop metastatic disease. Improvements in our understanding of the molecular basis of lung cancer have led to the development of targeted agents resulting in a significant clinical benefit. At present, this benefit is confined only to patients with particular molecular tumor characteristics. For all patients, chemotherapy represents the backbone of treatment and is associated with a significant overall survival prolongation and quality of life improvement. The purpose of this paper is to present the current landscape of chemotherapy for advanced non-small-cell lung cancer.